Propaganda negativa e judicialização da política no horário eleitoral presidencial de 2002 - Steibel, Fabro Boaz (2006)
This work intends to study the phenomenon of judialization of politics in Brazil, and intend to suggest that negative advertising needs to be more studied here. Initially, this work present the theoretical approach to negative campaign, identifying the im-balance of the Brazilian academy in disparity with preference that Judiciary Power, journalists and politicians dedicates to the subject. Moreover, the international debate instigate a categorization of negative campaign. At a second moment, this work ex-amine the judialization of politics in Brazil, and advocate that the Right of Reply needs to be more studied. In addition, the chapters present the origins of the Right of Reply and portray reservations about its application to politics campaigning. Finally, the work analyzes the presidential campaign of 2002, observing the Right of Reply requests and the negative campaigns propagated by Lula, Serra, Ciro and Garotinho in television.